Analysis of the Utilization of Animated Videos About Morals to Prevent Bullying Behavior in Early Childhood - Isnaini, Indri Dwi; Hariyani, Indaria Tri; Ariyanti, Mira Pradipta; Julianingsih, Denok; Anjani, Salsya Nabiilah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2025)
Good moral habits are mandatory for children to have from an early age. The most appropriate time to develop children's morals is when they are 0-6 years old. Where all aspects develop very rapidly, especially through very enjoyable media such as animated videos used in this study. The animated videos used in this study are sourced from the YouTube channel Kartun ini Budi. The purpose of utilizing animated videos about morals is to prevent bullying which is increasingly disturbing in the children's environment . The research method used in this study is descriptive qualitative using primary data analysis techniques (observation, interviews, documentation) and secondary (articles and reference books) . The results of this study were obtained from data reduction which stated that children who previously did not know what morals were found it easier to understand because they saw or watched animated videos directly. In the animated video, it tells various kinds of good and bad behavior and their consequences. By children seeing it directly, they know and are afraid to do bad things such as bullying by teasing friends or not respecting each other.